Infographic posters for enhancing 21st century communication skills - DeWitt, Dorothy; Alias, Norlidah (2017)
One of the problems among graduate students in a research methodology course is reading large numbers of articles during the course. Reading many research articles is required for an overview of current research methods and to determine the contribution of the findings to the field of knowledge. However, this task is overwhelming for students who felt that it was not meaningful reading these articles. Hence, one method to make the task meaningful is for students to present these reading assignments as an infographic and shared among the students in the course. In this way more students would be able to have access and read more research papers. In this study, a case study methodology was employed to investigate the case of four students who used infographic posters for presentation in the classroom. The students participated in the reading assignment and summarized the information in an infographic poster, which was shared on the course platform. The findings indicate that the learners developed the 21st century communication skills as well as literacy skills for summarizing main points. In addition, the other students in the course also managed to view the research papers in the infographic poster. In conclusion, infographic posters could be used for enhancing communication skills. Further research should be done to determine if it could be implemented in other courses and in enhancing other skills among learners.